(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Rapid societal changes drive the integration of social innovations into the social services sector. Demographic shifts, population aging, increasing social inequality, and ongoing challenges related to service accessibility and sustainability necessitate innovative solutions to enhance the efficiency and effectiveness of social services. The challenges of globalization further encourage a shift from traditional service delivery models. Social innovations, characterized by novel operational methods, collaborative governance models, and technological advancements, provide opportunities to improve service quality, accessibility, and long-term sustainability. These innovations not only address pressing social issues but also play a crucial role in strengthening community resilience, reducing social exclusion, and fostering inclusive development. Despite the potential of social innovations, their implementation faces numerous obstacles, including financial constraints, bureaucratic inertia, institutional barriers, and the complexities of adopting technological solutions. The aim of this study is to assess the role of social innovations in the social services sector, identify key barriers to their implementation, and propose strategies to overcome these challenges. The study employs a qualitative research methodology, utilizing interviews and content analysis to provide a comprehensive examination of social innovation practices across various social service sector contexts. The findings reveal that integrating innovative solutions not only enhances the efficiency of social services but also drives broader social transformations—strengthening local communities, reducing social inequality, and increasing the resilience of social service systems in times of crisis. The study highlights the importance of interdisciplinary collaboration, continuous professional development for social service practitioners, and the creation of a more flexible institutional environment to support the expansion of innovations.